Examining the factors that influence customer's intention to use Ar-Rahnu among Segamat residents / Haidatul Nabila Shahrun - Shahrun, Haidatul Nabila (Faculty of Business and Management, 2019)
One of the familiar Islamic banking and finance products used for short-term collateralized borrowing is Islamic pawnbroking or also known as Ar-Rahnu. Nowadays, the cost of living is increasing and most of the banking system has a strict procedure of financing. Both of these factors lead to the introduction of Ar-Rahnu in the financing field in Malaysia as one of the alternative ways for lower income group to borrow money quickly and easily without bear any higher cost of profit rate. The development of Ar-Rahnu in Malaysia provides an alternative pawnbroking service for borrowers, which is in accordance to syariah principles. This study is focuses on the customer intention to use Ar-Rahnu among Segamat residents. A survey comprised of 250 respondents was carried out. In addition, the use of syariah view, customer attitude, pricing system and customer service as the factors will helps the researcher to find out the most factors that influence factor customer's intention to use Ar-Rahnu. A structured question was designed where the data was analyzed by using reliability, correlation and multi regression analysis. Results show that syariah view is the most influential variable customer's intention to use Ar-Rahnu. While, the others factor such customer attitude, pricing system and customer service give a moderate impact. The result from multiple regression shows that the only factor that not significant is customer service. Recommendation for the future research is security and confidentiality can be used as one of the determinants to predict customer's intention to use Ar-Rahnu. In conclusion, this study is useful for the any Ar-Rahnu outlet to planning better Ar-Rahnu service for their customers in order to attract more customers to use their service.